Peningkatan Partisipasi Masyarakat dalam Musrenbang Desa Meunasah Teungoh Melalui Grup WhatsApp - Iqbal, Taufiq; Muliadi, Mus (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
Community service activities in Meunasah Teungoh Village aim to increase community participation in the Development Planning Deliberation (Musrenbang) through the use of digital technology, especially WhatsApp groups. This study adopted a participatory approach involving all elements of society, including traditional leaders, youth, and women, to ensure inclusivity in the development planning process. The methods used included an initial survey to identify the level of community awareness and digital literacy, digital literacy training, and collecting aspirations through the polling feature in the WhatsApp group. The results of the activities showed a significant increase in community participation, from 40% in 2023 to 72% in 2024, with a total of 58 proposals collected. The community satisfaction survey also showed that 85% of residents were satisfied with the transparency of information conveyed through the WhatsApp group. However, 15% of residents were dissatisfied, indicating room for improvement. This study concludes that the use of digital technology can strengthen community participation in the development planning process and recommends the need for mitigation strategies to address dissatisfaction and increase accessibility for all residents. This activity is expected to be a model for other villages in implementing the principles of participatory and sustainable development.